HABITAT PRIMATA DI STASIUN PENELITIAN KETAMBE, TAMAN NASIONAL G. LEUSEUR, ACEH - MIRMANTO, EDI (BERITA BIOLOGI, 1986)
EDIMIRMANTO.1986, The habitat of primates at the Ketambe Research Station, G. Leuseur National Park, Aceh. Berita Biologi 3(5): 232-239.A phytosociological analysis of the habitat of primates in Ketambe area, was conducted, using point-centered quarter method.Three groups of samples in ordination of Bray & Curtis were recognized.The groups are represent three community types, i.e. Aglaia-Paranephelium community, Dysoxylum-Aglaia community and Shorea Parashorea community.These three community types are useful for their survival of primates, as source of food as well as transportation support.